Efeito da suplementação de cobalto na biodigestão anaeróbia de vinhaça de cana-de-açúcar em reator termofílico de leito estruturado - Soares, Marcela Graziele (2015)
In this study, the effect of cobalt dosage on the performance of a thermophilic anaerobic structured bed reactor fed with vinasse sugarcane was investigated. The experiments were divided into three phases. In Phase 1, the reactor was submitted to an increasing volumetric organic load (OLR), starting with 2 and reaching 10 gCOD l-1 d-1. In Phase 2, the reactor was subjected to an OLR of 10 gCOD l-1 d-1 and an addition of CoCl2, with Co2+ concentrations of of 1, 2, 3, 4, 5, and 6 mg l-¹. In Phase 3, supplemental Co2+ was suppressed in order to verify the system's dependence on the micronutrient, or if the Co2+ retained in the biofilm during supplementation would still be causing positive effects in the treatment of vinasse. At the end of Phases 1 and 3 was performed the spatial profile for the apparent first order rate constants (K1), to verify that the vinasse was no change in reaction speed. The values of soluble COD removal and biogas production in Phase 1 increased proportionally to the increase of the pit, reaching the maximum value of 74% and 190,6 ml h -1, respectively, at the end of the Phase 1 operation. In the operation of Phase 2, it was observed that the cobalt supplementation positively affected the structured bed reactor. The COD conversion reached a maximum value of 100% during the supplementation of 5 mgCo2+ l-1, along with a higher value of PVM, 124,0 mlCH4 h-1 l-1. The biogas flow rate reached an average of 231,2 ml h-1, which reflects an average increase of 17,6% compared to Phase 1. In Step 3, it was possible to observe a decrease of 5,4% in the removal of soluble COD, compared to the cobalt supplementation phase and an increase in the biogas production of 8,8% compared with the same phase. This increase is probably due to the accumulation of cobalt in the mud, causing an increase in the specific activity of the methanogenic archaeas thus, the system accumulated less acid intermediates during the degradation of vinasse. The values of apparent first order rate constants for removal of COD (K1) in the profiles of Phase 1 and Phase 3 were of 0,0580 and 0,0955 h-1, respectively, which represents a significant increase in the reaction speed in Phase 3, when compared to Phase 1, confirming the hypothesis of cobalt accumulation in the mud after the suppression of cobalt, showing the positive effect of cobalt supplementation on the kinetics of the anaerobic process. The average output power was increased by 31,0% (Phase2) and 25,4% (Phase 3), regarding the last step of Phase 1 (OLR of 10 gCOD l-1 d-1). The cobalt supplementation affects positively the thermophilic anaerobic treatment of vinasse, having the greatest effect on the biogas production, however not on the increase of the methane fraction in the generated biogas. This effect is due to an increase in the removal of OLR, promoted by the cobalt supplementation, which reached an increment of 44% when applied a supplementation of 5 mgCo2+ l-1.